Narrative Review Encouraging Factors of Mothers to Carry Out Gentle Birth Program - Vanessa Alivia Savira; Yulizawati Yulizawati; Hardisman Hardisman (Universitas Andalas, 2022)
Childbirth is considered a frightening and painful process for most pregnant women, especially primiparas. This causes pregnant women to choose cesarean delivery. A gentle birth program is an approach to care for pregnancy and childbirth that helps mothers overcome their anxiety in dealing with childbirth. This study aimed to determine the factors that encourage mothers to carry out a gentle birth program.This type of research is a narrative literature review. The research was conducted from October to December 2021. Article searches were accessed through the PubMed, ScienceDirect, and Google Scholar databases. Articles were selected based on inclusion and exclusion criteria.The analysis was carried out on ten research articles. The results of internal factors that encourage mothers to carry out a gentle birth program are the mother's knowledge, mother's interest, mother's motivation, mother's perception, mother's experience of childbirth, mother's psychological aspect, and mother's belief in her abilities. Meanwhile, external factors encouraging mothers to carry out a gentle birth program are the husband's support, support from health workers, family and friends, and health facilities.The mother's knowledge is the dominant internal factor that encourages mothers to carry out a gentle birth program. Meanwhile, the husband's support is the dominant external factor that encourages mothers to carry out a gentle birth program